Platelet transfusion refractoriness within one month post-hematopoietic stem cell transplantation does not impair survival in aplastic anemia patients after engraftment: a propensity score-matched analysis - Wang, Yan; Zhang, Yuanfeng; Liu, Li; Zhang, Tingting; Sun, Jiali; Chen, Xin; Yang, Donglin; Pang, Aiming; Zhang, Rongli; Ma, Qiaoling; Zhai, Weihua; He, Yi; et al. (Frontiers in Immunology, 2025)
IntroductionThe incidence of platelet transfusion refractoriness (PTR) and its impact on survival outcomes in patients with severe aplastic anemia (SAA) undergoing allogeneic hematopoietic stem cell transplantation (allo-HSCT) remains unclear.MethodsWe investigated the incidence of early PTR (within one month post-allo-HSCT) and its clinical implications in 215 aplastic anemia (AA) patients in a retrospective study.ResultsAmong the enrolled patients, 24 (11.7%) developed PTR within the first month post-transplantation. Propensity score matching (PSM) was performed, resulting in 24 PTR cases and 96 matched non-PTR controls, with balanced baseline characteristics. No significant differences were observed between the two groups in bloodstream infections, grade II–IV or III–IV acute graft-versus-host disease (aGVHD), viral infections, or engraftment rates. However, PTR patients required significantly more red blood cell (median: 13.5 units vs. 8 units, P = 0.003) and platelet transfusions (median: 10.5 units vs. 5 units, P < 0.001) compared to non-PTR patients. The 3-year overall survival (OS) rate was numerically lower in the PTR group (66.7%; 95% CI, 44.3–81.7) than in the non-PTR group (81.2%; 95% CI, 71.1–88.0), although this difference was not statistically significant (P = 0.106). Multivariate analysis identified haploidentical donor and patient age as independent risk factors for OS.ConclusionOur findings suggest that early PTR occurs at a relatively low frequency (11.7%) in AA patients post-allo-HSCT and may not significantly compromise survival outcomes following successful engraftment.